Don’t Let Vine Weeds Trip You Up - Kanissery, Ramdas; McAvoy, Camille (EDIS, 2018)
Weedy vines are among the problematic group of weeds in citrus due to their aggressive growth and difficulty in management. They compete for resources and hinder harvesting operations. Management options available for vine weed management in citrus include the combination of preventive, physical, and chemical control. This article is intended to provide growers with some insights towards managing vine weeds in citrus production.